Blood Cultures Versus Respiratory Cultures: 2 Different Views of Pneumonia. (29th October 2019) - Haessler, Sarah; Lindenauer, Peter K; Zilberberg, Marya D; Imrey, Peter B; Yu, Pei-Chun; Higgins, Tom; Deshpande, Abhishek; Rothberg, Michael B
Abstract: Background: Choice of empiric therapy for pneumonia depends on risk for antimicrobial resistance. Models to predict resistance are derived from blood and respiratory culture results. We compared these results to understand if organisms and resistance patterns differed by site. We also compared characteristics and outcomes of patients with positive cultures by site. Methods: We studied adult patients discharged from 177 US hospitals from July 2010 through June 2015, with principal diagnoses of pneumonia, or principal diagnoses of respiratory failure, acute respiratory distress syndrome, respiratory arrest, or sepsis with a secondary diagnosis of pneumonia, and who had blood or respiratory cultures performed. Demographics, treatment, microbiologic results, and outcomes were examined. Results: Among 138 561 hospitalizations of patients with pneumonia who had blood or respiratory cultures obtained at admission, 12 888 (9.3%) yielded positive cultures: 6438 respiratory cultures, 5992 blood cultures, and 458 both respiratory and blood cultures. Forty-two percent had isolates resistant to first-line therapy for community-acquired pneumonia. Isolates from respiratory samples were more often resistant than were isolates from blood (54.2% vs 26.6%; P < .001). Patients with both culture sites positive had higher case-fatality, longer lengths of stay, and higher costs than patients who had only blood or respiratory cultures positive. Among respiratory cultures, the most common pathogens were Staphylococcus aureus (34%) and Pseudomonas aeruginosa (17%), whereas blood cultures most commonly grew Streptococcus pneumoniae (33%), followed by S. aureus (22%). Conclusions: Patients with positive respiratory tract cultures are clinically different from those with positive blood cultures, and resistance patterns differ by source. Models of antibiotic resistance should account for culture source. Abstract : Patients with positive respiratory tract cultures are clinically different from those with positive blood cultures and the resistance patterns differ by culture source. Models of antibiotic resistance should account for culture source.